Older Adults’ Participation in VIAS’ Mobile App Design - Gomes, Cristina Azevedo (2021)
The literature is consensual when it tells us that the choice of the intergenerational approach brings significant advantages, both for the youngest, the oldest and even for the technological products under development. Given this reality, this article describes some of the intergenerational workshops developed within the ViseuInterAgeStories Project (VIAS), although with a special focus on the participation of the elderly. VIAS promotes collaboration between children and the elderly in the creation of georeferenced stories in a mobile application while touring places of culture, heritage and a natural interest in the city of Viseu. To do so, they can publish local images, texts or audios or access stories already shared by other users, creating a city identity network. The project followed a Participatory Design approach, involving children and older adults during intergenerational dynamics and practices and to co-design the app. The results reveal the appreciation of the city’s history by the seniors and the importance of thematic categorization in the organization of the mobile application. Thus the App integrates georeferenced historical information. Even assuming difficulties in using the technology, participants built meaningful ideas of what they wanted and could get from it. Intergenerational experience and the co-design process have revealed positive implications for self-esteem and satisfaction among older people.